2021
DOI: 10.3389/fpsyg.2021.573846
|View full text |Cite
|
Sign up to set email alerts
|

Further to the Left: Stress-Induced Increase of Spatial Pseudoneglect During the COVID-19 Lockdown

Abstract: BackgroundThe measures taken to contain the coronavirus disease 2019 (COVID-19) pandemic, such as the lockdown in Italy, do impact psychological health; yet, less is known about their effect on cognitive functioning. The transactional theory of stress predicts reciprocal influences between perceived stress and cognitive performance. However, the effects of a period of stress due to social isolation on spatial cognition and exploration have been little examined. The aim of the present study was to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 60 publications
3
24
0
Order By: Relevance
“…Over the last year, the spread of COVID-19 pandemic has imposed even more changes and challenges in university students’ daily life ( Aristovnik et al, 2020 ). Specifically, several studies have broadly explored the impact of the COVID-19 on university students’ lives, underlining a wide spread of different psychological symptoms ( Li et al, 2021 ), such as stress and difficulties in concentrating ( Son et al, 2020 ; Zurlo et al, 2020 ; Baltà-Salvador et al, 2021 ; Lardone et al, 2021 ; Somma et al, 2021 ), anxiety and depression ( Cao et al, 2020 ; Husky et al, 2020 ; Galvin et al, 2021 ; Rusch et al, 2021 ), eating disorders, alcohol/substance abuse ( Gritsenko et al, 2020 ; Browning et al, 2021 ; Charles et al, 2021 ), sleep disorders ( Debowska et al, 2020 ), and suicidal behaviors ( Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last year, the spread of COVID-19 pandemic has imposed even more changes and challenges in university students’ daily life ( Aristovnik et al, 2020 ). Specifically, several studies have broadly explored the impact of the COVID-19 on university students’ lives, underlining a wide spread of different psychological symptoms ( Li et al, 2021 ), such as stress and difficulties in concentrating ( Son et al, 2020 ; Zurlo et al, 2020 ; Baltà-Salvador et al, 2021 ; Lardone et al, 2021 ; Somma et al, 2021 ), anxiety and depression ( Cao et al, 2020 ; Husky et al, 2020 ; Galvin et al, 2021 ; Rusch et al, 2021 ), eating disorders, alcohol/substance abuse ( Gritsenko et al, 2020 ; Browning et al, 2021 ; Charles et al, 2021 ), sleep disorders ( Debowska et al, 2020 ), and suicidal behaviors ( Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This chronic stress exposure lead to an increase in asymmetry in turning behavior in rats that were exposed to high levels of stress. Similarly, Somma et al (2021) found that stress related to a Covid-19 related lock-down increased leftward bias in spatial perception. This indicated that long-term exposure to stress changes behavioral asymmetries.…”
Section: Discussionmentioning
confidence: 81%
“…In summary, evidence on the effects of self-reported affect and traits on pseudoneglect show that positive affect [40] and positive attitude [44] are correlated with a rightward bias. Moreover, greater self-reported claustrophobic fear is related to a rightward bias when the line bisection is performed at a short distance [46].…”
Section: Emotional Traits Hormones Stress and Spatial Distancementioning
confidence: 92%
“…Somma et al [44] conducted a longitudinal study on the effects of stress on pseudoneglect induced by the strict lockdown rules during the COVID-19 pandemic in Italy. The authors asked subjects to perform a computerized cancellation task (i.e., to cancel all the stimuli as fast as possible using a stylus pen touch or a mouse click) one week before the start of the lockdown and during the following two months during the lockdown.…”
Section: Emotional Traits Hormones Stress and Spatial Distancementioning
confidence: 99%